EKSPLORASI KONSEP PEMBELAJARAN “CREATIVEPRENEURSHIP” DEMI KEEFEKTIFAN PROGRAM PENDIDIKAN KEWIRAUSAHAAN DALAM UPAYA MENSTIMULASI NIAT WIRAUSAHA MAHASISWA - Rahmi, Vembri Aulia (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
Unemployment and economic instability are still burdening in Indonesia. As the policy authorities, the government has initiated to develop the "National Entrepreneurship Movement" programme, which refers to several aspects of entrepreneurial-oriented life. University of Muhammadiyah Gresik as an educational institution also have followed to the government program through entrepreneurship  education program. This research is descriptive research with qualitative method. The implementation of the concept of learning is applied to business and nonbusiness study programs that is conceptualized both conventional and creativepreneurship. The results suggest that in order to create the effectiveness of entrepreneurship education program, it takes collaboration of entrepreneurship learning concept, that is synergy between lecturer and student of business study program and nonbisnis. Based on student perception who obtained by  face to face in-depth interview, the mostly student stated that entrepreneurship education program  can  strongly  support  to stimulate entrepreneurial intention of the students of Gresik Muhammadiyah University since the early.